A Efetividade do direito à saúde no brasil: temas atuais sobre a disponibilização do direito à saúde na perspectiva do Supremo Tribunal Federal - FERNANDES, Luciana Barros (2022)
The objective of this monograph is to study the effectiveness of the right to health, for that it was necessary to conceptualise the right to health; Approach the way the Brazilian Constitution of 1988 provides the right to health as a fundamental right and what its promotion is; Seeking to understand arguments involving the Principle of Basic conditions of Life and the Principle of Reserve for Contingences; To seek understanding of the phenomenon of the judicialisation of the right to health and the importance of the Judiciary participation in public policies; Collect legal precedents and themes of general repercussion that demonstrate the Federal Supreme Court's perspective on the effectiveness of the right to health; Analyse the rights and duties of Individuals and the State in the right to health using the Pandemic caused by the COVID-19 as an example. In this regard, the method adopted was that of bibliographic research and thus carried out an analytical-descriptive research using books, electronic sites, judgments and regulations, in addition, this monograph analysed the effectiveness of the right to health through the approach of some of the current themes on this social right, being the themes as following: Principle of Basic conditions of Life, Principle of Reserve for Contingences, Essential Core of the Right to Health and the Pandemic caused by COVID-19. From this analysis, we observed the benefits of the active position of the Judiciary in the phenomenon of the judicialisation of the right to health, since the Executive and Legislative Powers would be omitting in relation to a right to do and society needs an answer to the complex health situation of the country. Therefore, it was possible to deduce from the research that the State has a duty to provide the right to do in relation to public policies that make this fundamental right concrete, thus, the effectiveness of the right is not limited to curative medicine, since actions and services must also be carried out for prevention and promotion.